Influence of Entrepreneurial Orientation on Venture Capitalists' Initial Trust - Yang, Hongtao; Zhang, Lei; Wu, Yenchun Jim; Shi, Hangyu; Xie, Shuting (Frontiers in Psychology, 2021)
The effectiveness of trust has been extensively investigated in entrepreneurship studies. However, compared to the outcomes of trust, we still lack knowledge about the mechanisms underlying venture capitalists’ initial trust in entrepreneurs. Drawing from signal theory and impression management theory, this study explores an impression management motivational explanation for the influencing factors of venture capitalists’ initial trust. An empirical test is based on 202 valid questionnaires from venture capitalists, and the results indicate that the five dimensions of entrepreneurial orientation have a significant impact on the initial trust of venture capitalists, and that an entrepreneurial orientation of perseverance or passion positively influences venture capitalists’ initial trust through acquired impression management strategies, while an entrepreneurial orientation of risk-taking, innovation, or proactivity positively affects the initial trust of venture capitalists through defensive impression management strategies. The perceptions of entrepreneurs’ hypocrisy by venture capitalists negatively moderate the relationship between acquired impression management strategies and the initial trust of venture capitalists, and negatively moderate the relationship between defensive impression management strategies and the initial trust of venture capitalists.